Fake News no Facebook: a desinformação no cenário eleitoral brasileiro de 2018 - Rodrigues, Shirley Maria de Oliveira (2019)
The False news is always present in society that impacts the process of opinion formation. This phenomenon that today presents itself as a new nomenclature of fake news accompanied by the development of society and especially digital social media, which is found as a breeding ground for common sense testing and social interactions where this news is shared. among people who believe in the sender of the information, for its proximity. Given this, the present study aimed to address the phenomenon of false news and its contributions to political discourse, taking as its main point false news shared by voters of Jair Bolsonaro during a 2018 election campaign. This paper is presented as implications. In this news false opinions in public opinion and its unfolding in the electoral scenario, making a historical survey of false news in various periods of our society to this day, highlighting this false news attacks directly as fundamental bases of information science and citizenship. This research was approached qualitative because it allowed the research of an object with object of study to answer proposed objectives, finally, that uses a content analysis to analyze false posts and how they were used for fin voters. In the concluding remarks, an analysis is made of how much false news undermines the critical sense of the device, leading to a loss of quality in the political debate.